High-Power Lasers and Light–Matter Interactions - Zhaohong Liu; Sensen Li; Jiawei Sun (Photonics)
High-power laser systems and the study of light–matter interactions at high intensities are crucial for numerous scientific and technological fields, ranging from industrial materials processing [...]